This State of wonders : the letters of an Iowa frontier family, 1858-1861 - Folmar, John Kent, 1932- (Bur oak book., 1986)
When the John Hugh Williams family immigrated to Homer, Iowa, in the 1850s, they had six children, ranging in age from five to twenty. Suddenly land poor, in debt, and caught in the Panic of '57, they sent their eldest son, James, to Georgia to work and add to the family income. The seventy-five letters collected here represent the family's correspondence to their absent son and brother. From 1858 to 1861, James' sisters, brothers, mother, and father wrote to him frequently, each with distinct views on their daily life and struggles. While Mr. Williams wrote most often about money, farm.